School Education Management: Navigating Policy Intent and Local Managers’ Practice in Federal Nepal - Thapa, Dharma Jung (The Journal of DMC, 2026)
The 2015 Constitution of Nepal restructured the nation into a federal republic, terminating the constitutional monarchy and unitary governance system. This transformation was intended to facilitate socioeconomic progress through decentralization and inclusion of education. However, the strategic adaptation of this system is fundamentally constrained by an interrelated system of barriers, where structural deficits, a legislative vacuum, and political interference have hindered the effective management of school education. This cycle systematically reconcentrates power and stifles local initiatives. This qualitative case study explores how education managers understand, interpret, and implement decentralized education policies in the management of school education in Nepal. Grounded in decentralization and federalism theories, this study examines the tensions and innovations that arise between policy intentions and local-level implementation. Data were collected through interviews and participatory observations with 12 stakeholders, including a mayor, rural municipality chairs, and education officers from three strategically selected local governments. The analysis reveals local innovations, such as context-specific education policies and teacher training programs, while identifying significant challenges, including budget dependency, political interference, and weak intergovernmental coordination. The findings suggest that centralist tendencies, incomplete policies, and fragmented institutions hinder effective decentralization. This study contributes to the debate on the need for clear, Constitution-aligned policies to support federal transition and ensure effective school management